Tradisi Belis Dalam Perkawinan Adat Suku Uma Metan Desa Sisi Kecamatan Kobalima Kabupaten Malaka (Suatu Tinjauan Deskriptif Historis) - Antonius Bere; Indri Septiyana; Reynaria Klara Klau; Augusta De Jesus Magalhaes (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to determine the belis tradition in the customary marriage of the Uma metan tribe, Sisi Village, Kobalima District, Malacca Regency with a historical descriptive review, and to describe the social and economic impacts of the high belis phenomenon. This research uses a qualitative descriptive research type. In the Uma Metan tribe, there is the Kletek Truik traditional marriage which has various provisions regarding the granting of belis to prospective wives. The buying process is inseparable from the agreement between the families. The process of giving belis involves both parties, both the male family and the female family, to provide reciprocal belis so that a good family relationship will be established so that no party is harmed. To be able to influence and maintain the life of the Uma Metan people, because this influence is closely related to individual life such as self-esteem in the family and self-confidence to pay off the belis. The results of his research are that the belis tradition in the Uma Metan tribe must be preserved but even more simplified and what is seen as a value that has essential meaning is maintained, namely that which symbolizes a system of social exchange to express respect for the dignity of a woman's position as a wife, expression of affection for children towards parents who have educated and raised as well as expressions of solidarity between the two umas concerned. Because in the current era, different types of belis, such as silver coins, plates (belak), softren, and muti leaves (morteen) in traditional houses, have started to disappear (disappear) so that everything is cashed out, this causes it to become a burden (debt) for the parties. men with a mediocre economy. So that it has social and economic impacts on the lives of individuals and their families.